From individual attitudes towards migrants to migration policy outcomes: theory and evidence - Giovanni Facchini; Anna Maria Mayda (Institute for the Study of Labor (IZA), 2008)
In democratic societies individual attitudes of voters represent the foundations of policy making. We start by analyzing patterns in public opinion on migration and find that, across countries of different income levels, only a small minority of voters favour more open migration policies. Next we investigate the determinants of voters' preferences towards immigration from a theoretical and empirical point of view. Our analysis supports the role played by economic channels (labour market, welfare state, efficiency gains) using both the 1995 and 2003 rounds of the ISSP survey. The second part of the paper examines how attitudes translate into a migration policy outcome. We consider two alternative political-economy frameworks: the median voter and the interest groups model. On the one hand, the restrictive policies in place across destination countries and the very low fractions of voters favouring immigration are consistent with the median voter framework. At the same time, given the extent of individual-level opposition to immigration that appears in the data, it is somewhat puzzling, in a median-voter perspective, that migration flows take place at all. Interest-groups dynamics have the potential to explain this puzzle. We find evidence from regression analysis supporting both political-economy frameworks.
urn:nbn:de:101:1-2008060579
Keywords: F22; 330; Immigration; immigration policy; median voter; interest groups; political economy; Gesellschaft; Gesellschaftliches Bewusstsein; Wahlverhalten; Migrationspolitik; Median Voter; Welt